2008
DOI: 10.1007/s11230-008-9146-6
|View full text |Cite
|
Sign up to set email alerts
|

A revision of Petasiger Dietz, 1909 (Digenea: Echinostomatidae) and a key to its species

Abstract: Petasiger Dietz, 1909 is revised, and a key to and lists of the records and hosts of the 18 recognised species are presented. The recognised species are: P. exaeretus Dietz, 1909, P. australis Johnston & Angel, 1941, P. combesi Zamparo, Overstreet & Brooks, 2005, P. floridus Premvati, 1968, P. grandivesicularis Ishii, 1935, P. islandicus Kostadinova & Skirnisson, 2007, P. johnstoni n. sp., P. megacanthus (Kotlán, 1922), P. minutissimus Gogate, 1934, P. neocomense Fuhrmann, 1927, P. nitidus Linton, 1928, P. nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 21 publications
4
42
0
Order By: Relevance
“…These differences may result from the use of uncompressed specimens in this study. Despite the noted size differences, other differential characteristics, such as the equivalent sizes of the anterior and posterior portions of the parasite, the similar widths of the cirrus pouch and the ventral sucker, the presence of vitellaria that are confluent in the region below the ventral sucker, the tandem positioning of the testes, and the arrangement and size of the collar spines, are in agreement with those reported for P. novemdecim (LUTZ, 1928;NASIR et al, 1972;FALTÝNKOVÁ et al, 2008). In addition, the specimens examined in this study have larger dimensions than those reported for P. argentinensis.…”
Section: Speciessupporting
confidence: 86%
See 4 more Smart Citations
“…These differences may result from the use of uncompressed specimens in this study. Despite the noted size differences, other differential characteristics, such as the equivalent sizes of the anterior and posterior portions of the parasite, the similar widths of the cirrus pouch and the ventral sucker, the presence of vitellaria that are confluent in the region below the ventral sucker, the tandem positioning of the testes, and the arrangement and size of the collar spines, are in agreement with those reported for P. novemdecim (LUTZ, 1928;NASIR et al, 1972;FALTÝNKOVÁ et al, 2008). In addition, the specimens examined in this study have larger dimensions than those reported for P. argentinensis.…”
Section: Speciessupporting
confidence: 86%
“…Petasiger novemdecim P. caribbensis P. argentinensis Reference Present study Nasir et al, 1972Faltýnková et al, 2008Nassi, 1980Lunaschi and Drago, 2010 The specimens of P. novemdecim that were obtained from T. dominicus in Brazil have smaller measurements for some body structures than those reported for the species by other authors. These differences may result from the use of uncompressed specimens in this study.…”
Section: Speciesmentioning
confidence: 71%
See 3 more Smart Citations